Inheritance of Yield and its Components in Safflower (CARTHAMUS Tinctorius L.) - Gupta, R K; Singh, S P (Annals of Arid Zone, 2016)
Parents, Fl, F2 Bl and B2 generations of 10 crosses from 5 parents were studied to estimate the gene effects for seed yield and yield components in safflower (Carthamus tiflctorius L.). Scaling te;ts suggest the non-allelic interaclion for all the crosses and characters. Dominance effect(h) was more pronounced than additive effect (d) in almost all the crosses. Epistatic effects were found for all crosses. The duplicate type epistasis was more frequent than complementary. Considering the gene actions, recurrent selection may be utilized to improve the seed yield through component traits.